2014
DOI: 10.1016/j.socscimed.2014.03.029
|View full text |Cite
|
Sign up to set email alerts
|

The multiple truths about crystal meth among young people entrenched in an urban drug scene: A longitudinal ethnographic investigation

Abstract: Transitions into more harmful forms of illicit drug use among youth have been identified as important foci for research and intervention. In settings around the world, the transition to crystal methamphetamine (meth) use among youth is considered a particularly dangerous and growing problem. Epidemiological evidence suggests that, particularly among young, street-involved populations, meth use is associated with numerous sex- and drug-related “risks behaviors” and negative health outcomes. Relatively few studi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
36
1
6

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(45 citation statements)
references
References 53 publications
(69 reference statements)
2
36
1
6
Order By: Relevance
“…Particularly in rural areas of the counties, social marginalization, lack of opportunities, and intergenerational patterns of drug use created the social and emotional conditions conducive to initiating drug use (Fast, Kerr, Wood, & Small, 2014; Gracia 2010). Meso-level social contextual factors were critically important in our participants’ accounts of methamphetamine use, with factors including psychological distress, family influences, intimate relationships, and exposure to others who inject all playing a prominent role in injection trajectories.…”
Section: Resultsmentioning
confidence: 99%
“…Particularly in rural areas of the counties, social marginalization, lack of opportunities, and intergenerational patterns of drug use created the social and emotional conditions conducive to initiating drug use (Fast, Kerr, Wood, & Small, 2014; Gracia 2010). Meso-level social contextual factors were critically important in our participants’ accounts of methamphetamine use, with factors including psychological distress, family influences, intimate relationships, and exposure to others who inject all playing a prominent role in injection trajectories.…”
Section: Resultsmentioning
confidence: 99%
“…In multivariable analyses, physical/sexual violence independently predicted time to initiation of CM injection, which may imply that sex workers are self-medicating with CM for trauma or mental illness. Ethnographic research among street-involved youth in Vancouver supports this hypothesis, where narratives describe using CM as treatment for both professionally and self-diagnosed mental illness (Fast et al, 2014). A systematic review demonstrated consistent associations between CM use and psychosis and depression among youth (Marshall and Werb, 2010).…”
Section: Discussionmentioning
confidence: 97%
“…Among the limited available data, there is evidence to suggest that harms associated with CM use are increasing in marginalized street-involved populations (e.g., youth) in Western Canada (Degenhardt et al, 2010; Fast et al, 2014; Wood et al, 2006). In Vancouver, Canada, the use of CM has risen among various injection and non-injection drug-using populations (Wood et al, 2006) and recently, the prevalence of CM injection among adults in Vancouver doubled from 4.9% to 10.5% between 2010 and 2011 (UHRI, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Bezüglich Konsumentengruppen und -motiven von Methamphetamin existiert international eine recht gute Datenlage [13,21,23,24]. Studien zeigen, dass im Vergleich zu anderen illegalen Drogen beim Methamphetaminkonsum keine Begrenzung auf bestimmte Personengruppen feststellbar ist und riskante Konsummuster in verschiedenen sozialen Gruppen zu finden sind [21,23,24]. Neben Motiven wie Selbstwertsteigerung, Selbstmedikation, Steigerung sexueller Aktivität, Entspannung sowie um Spaß zu haben, konsumieren die Betroffenen Crystal Meth zur Leistungssteigerung im Beruf und Alltag [13,21].…”
Section: Introductionunclassified